Workforce Agility : Improving Employee Performance from the perspective of a Competitive Work Environment - Hamy Wahjunianto (Institute of Computer Science (IOCS), 2022)
This study aims to describe and examine the effect of a competitive environment perspective on workforce agility and its impact on employee performance—the population of employees in various branch offices of PT Kualita Media Tama. Sampling used the Slovin formula with a margin of error of 10% to obtain a quota of 124 samplings. Performance appraisal data was taken from HR Department documents, employee agility was measured from the Scaled Agile Framework (SAFe), and competitive environment perspective data was measured using the environment competitive scale (CES) Thurstone scale model. Data analysis used inferential statistics to describe each variable, and the decision-making hypothesis used linear regression analysis. The study's results prove that a competitive work environment affects workforce agility and employee performance. Workforce agility affects employee performance, and a competitive work environment through workforce agility affects employee performance. Workforce agility can contribute significantly more effectively than a competitive work environment to employee performance. The results of this study recommend that company management improve employee agility by establishing a competitive work environment as a means of organizational learning and through training.